2017
DOI: 10.3390/en10111763
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Bioethanol In Silico Production Process in a Fed-Batch Bioreactor Using Non-Linear Model Predictive Control and Evolutionary Computation Techniques

Abstract: Due to growing worldwide energy demand, the search for diversification of the energy matrix stands out as an important research topic. Bioethanol represents a notable alternative of renewable and environmental-friendly energy sources extracted from biomass, the bioenergy. Thus, the assurance of optimal growth conditions in the fermenter through operational variables manipulation is cardinal for the maximization of the ethanol production process yield. The current work focuses in the determination of optimal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…In numerous studies, predetermined exponential feed profiles (calculated based on initial conditions and growth kinetic parameters) are reported [33,34]. In recent studies, optimization of fed-batch operating conditions based on open loop strategy have been reported for recombinant lipase B, vaccine synthesis, ethanol, and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) production [34][35][36][37][38].…”
Section: Open Loop Controlmentioning
confidence: 99%
“…In numerous studies, predetermined exponential feed profiles (calculated based on initial conditions and growth kinetic parameters) are reported [33,34]. In recent studies, optimization of fed-batch operating conditions based on open loop strategy have been reported for recombinant lipase B, vaccine synthesis, ethanol, and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) production [34][35][36][37][38].…”
Section: Open Loop Controlmentioning
confidence: 99%
“…In this part, the colour histogram, derived of wavelet analysis of different reactions, is analysed. Table 3 shows the colour histogram of the two successful chemical reactions ( 1) and (2). The reaction result (1) has a bright colour and single colour component, while (2) with the double colour components.…”
Section: Colour Histogrammentioning
confidence: 99%
“…Table 3 shows the colour histogram of the two successful chemical reactions ( 1) and (2). The reaction result (1) has a bright colour and single colour component, while (2) with the double colour components. This shows that the result (2) contains some impurities (mucilages), while the result (1) shows a biodiesel in which there are no impurities, having a homogeneous colour.…”
Section: Colour Histogrammentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach was able to drive the system states to the desired set-points to maximize the biomass production, by considering the substrate concentration as the only available on-line measurement. In the work by De Freitas et al 28 the determination of the optimal control scheme for a fed-batch bio-ethanol process using evolutionary computation techniques is addressed. Results of this in silico study have shown once again that meta-heuristic algorithms (e.g.…”
Section: Introductionmentioning
confidence: 99%